Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1111/jbi.12378
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the paths leading to variation in geographical range size in western North American monkeyflowers

Abstract: Aim Closely related species can vary tremendously in size of geographical range, yet the causes of such variation are poorly understood. Prominent hypotheses about range size emphasize effects of niche properties and habitat connectivity via the amount and occupancy of suitable habitat, respectively. Previous studies have examined single hypotheses in isolation; however, we assessed the relative importance of these effects along with their potential interactions, using monkeyflower species (genus Mimulus) as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
64
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(65 citation statements)
references
References 53 publications
1
64
0
Order By: Relevance
“…Though experiments can only quantify niche breadth for a relatively small number of species and niche axes, they are a potentially powerful complement to verify tests of the niche breadth hypothesis based on correlative methods for a large number of species. For example, a study of western North American monkeyflowers found strong support for the climatic niche breadth hypothesis when using herbarium records to quantify both niche breadth and range size for 72 species (Sheth et al , ), and weaker support (possibly due to small sample sizes) when quantifying niche breadth experimentally with thermal performance curves for 10 of those species (Sheth & Angert, ).…”
Section: Equilibrial Limits: Variation In Ranges That Are Static Thromentioning
confidence: 99%
See 2 more Smart Citations
“…Though experiments can only quantify niche breadth for a relatively small number of species and niche axes, they are a potentially powerful complement to verify tests of the niche breadth hypothesis based on correlative methods for a large number of species. For example, a study of western North American monkeyflowers found strong support for the climatic niche breadth hypothesis when using herbarium records to quantify both niche breadth and range size for 72 species (Sheth et al , ), and weaker support (possibly due to small sample sizes) when quantifying niche breadth experimentally with thermal performance curves for 10 of those species (Sheth & Angert, ).…”
Section: Equilibrial Limits: Variation In Ranges That Are Static Thromentioning
confidence: 99%
“…Colors in the map correspond to the mean range size of species recorded in each grid cell. (b) Frequency distribution of range size for species of western North American monkeyflowers (redrawn from Sheth et al , ). As observed in many species assemblages, most species have small geographic ranges, and only a small number of species have large geographic ranges, but range size can vary dramatically even among closely related species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding how fitness and reproductive success vary across climate niche space could be an important avenue for future investigation, as it has been with density-dependent habitat selection (Morris, 1989;Sillett et al, 2004). While others have defined ecological niche as the set of conditions under which the intrinsic rate of increase is non-negative (Sheth et al, 2014), we make no statements here about fitness or growth rate and instead use the range of conditions occupied to define realized niche, as is consistent with ecological niche modelling (Pearson & Dawson, 2003;Sober on & Peterson, 2005) and niche theory (Pulliam, 2000). While others have defined ecological niche as the set of conditions under which the intrinsic rate of increase is non-negative (Sheth et al, 2014), we make no statements here about fitness or growth rate and instead use the range of conditions occupied to define realized niche, as is consistent with ecological niche modelling (Pearson & Dawson, 2003;Sober on & Peterson, 2005) and niche theory (Pulliam, 2000).…”
Section: Discussionmentioning
confidence: 88%
“…This expands long-standing ecological niche theory that occupied niche breadth increases with population growth (Vandermeer, 1972). Niche breadth has been used as a static, explanatory variable of population trends (Green et al, 2008;Jiguet et al, 2013) or geographical distribution (Sheth et al, 2014), or as a latent variable in the distribution-abundance relationship (Brown, 1984;Heino et al, 2008;Borregaard & Rahbek, 2010). Niche breadth has been used as a static, explanatory variable of population trends (Green et al, 2008;Jiguet et al, 2013) or geographical distribution (Sheth et al, 2014), or as a latent variable in the distribution-abundance relationship (Brown, 1984;Heino et al, 2008;Borregaard & Rahbek, 2010).…”
Section: Discussionmentioning
confidence: 99%